A convenient synthesis of phosphonomethyl α, β-unsaturated γ-lactams. Issue 40 (30th September 2015) - Abdelli, Abderrahmen; Efrit, Mohamed Lotfi; Gaucher, Anne; M'rabet, Hedi; Prim, Damien
Graphical abstract: Abstract: A versatile access to diversely substituted α, β-unsaturated γ-lactams is described using a common allylphosphonate precursor. The construction of the γ-lactam motive is based on two steps including a key sequential one-pot Michael addition–Nef sequence that allows the preparation of keto-ester intermediates. Our methodology allowed the selective installation of various alkyl, cycloalkyl and aryl substituents as well as a valuable phosphonomethyl fragment at positions 1 and 3 of the heterocycle.